Information and methodological support to the implementation of Best Available Techniques in the Russian Federation - D. O. Skobelev (Управление)
The aim, objectives and main directions of the information and methodological support for environmental and technological modernisation of Russian economy and its transfer to Best Available Techniques in key economic sectors have been analysed in the article. It has been indicated, that the environmental and technological modernisation corresponds with the national goals and strategic development objectives of the Russian Federation, namely: establishing highly-productive, export oriented, resource efficient industry on the basis of modern technologies.The new direction of development of industrial policy of Russia – environmental industrial policy has been considered. The experience in developing and applying information and methodological support instruments, including information workshops, role games and professional qualification enhancement programmes has been described. The role of expert society on Best Available Techniques in the implementation of the environmental industrial policy has been analysed. It has been emphasised, that objectives of informing a wide range of interested parties, improving professional qualifications, forming the expert society on Best Available Techniques, considering development of norms and standards, assessing modernisation costs and establishing the rationale for setting new technological parameters, their resource efficiency and environmental performance, – all these issues should be regarded as inter-related net of cross-linked solutions. It has been demonstrated, that research projects implemented within the framework of the information and methodological support for the modernisation of the economy, provide for obtaining and systematising information needed to set environmental and economic rationale for new requirements to the resource efficiency and environmental performance of key production processes. Practical approaches have been determined for enhancing public discussion and information dissemination tools, professional qualification improvement programmes, approaches to the discussion of draft norms in the field of Best Available Techniques and resource efficiency for economic entities with regulators and regulated community, as well as other stakeholders, at the national and regional levels.